Tanning beds: A call to action for further educational and legislative efforts. Issue 2 (17th July 2015) - Farley, Clara; Alimi, Yewande; Espinosa, Lauren R.; Perez, Sebastian; Knechtle, William; Hestley, Andrea; Carlson, Grant W.; Russell, Maria C.; Delman, Keith A.; Rizzo, Monica
<x xml:space="preserve">Abstract</x> Backgorund and objectives Melanoma is steadily increasing over the past decade. Recent studies confirmed a link between tanning bed use and melanoma. We sought to determine the prevalence and frequency of tanning bed among young patients with melanoma. Methods We retrospectively analyzed tanning bed use among young melanoma patients compared to controls selected from the hospital medical records. A telephone survey investigated family history of melanoma or skin cancer, hair color, eye color, skin type, tanning bed use, and patient awareness of dangers of tanning bed use. Results A total of 601 melanoma cases were identified; 265 (44%) completed the telephone survey as did 195 (31%) controls. Of these 460 subjects, 260 were female. Females were 3.0 times more likely to have used a tanning bed. Melanoma patients had natural light color hair, blue–green eyes, and 2.0 times more likely to use a tanning bed than controls. Among the tanning bed users, 90% were aware of danger of tanning bed. Conclusions Our study found that tanning beds were more likely to be used by young women, the majority of whom are aware of the associated risks. Eliminating the use of tanning beds should be considered to decrease the incidence of melanoma. J. Surg. Oncol. 2015 111:183–187. © 2015 Wiley Periodicals, Inc.